1500 V three‐level forward converter with phase‐shifted control. Issue 9 (3rd July 2018) - Hong, Feng; Li, Longchun; Wu, Yu; Ji, Baojian; Zhou, Yufei
Abstract : A 1500 V three‐level forward converter with phase‐shifted control is proposed to meet therequirements on medium‐ and high‐voltage DC bus of photovoltaic grid‐connectedsystem. The architecture of 1500 V DC bus is established by filtering thephase‐shifted outputs in series centrally, in which the internal filters of eachDC/DC converter are removed. The three‐level voltage is superimposed byphase‐shifting the rectified output voltages in series, which is beneficial todecrease the inductor current pulsation, diminish the ripple of output voltageand improve the system efficiency. The centralised filter contributes todownsizing the filter and reducing the system cost. With the introduction ofparallel‐series structure, the characteristics of low‐voltage stress areretained and the power transmission is improved. Meanwhile, the minimum value oftotal harmonic distortion (THD) with phase‐shifted control is obtained throughthe Fourier decomposition of three‐level voltage waveform. By analysing thevariation rule of THD with the change of conduction angle, the optimalsteady‐state operating point of the converter is achieved. The operatingprinciple of the proposed system is presented minutely in this study and aprototype has been established. The experimental results verify the validity ofthe proposed converter.